London - Dragicevich, Peter; Fallon, Steve; Filou, Emilie; harper, Damian (Lonely Planet guidebooks., 2016)
Provides information on major points of interest, activities, accomodations, restaurants, shopping, transportation, and entertainment in the city of London.